2011
DOI: 10.5194/tc-5-539-2011
|View full text |Cite
|
Sign up to set email alerts
|

Favorable climatic regime for maintaining the present-day geometry of the Gregoriev Glacier, Inner Tien Shan

Abstract: Abstract. We conducted 2 yr (2005)(2006)(2007) of in situ meteorological and glaciological observations on the Gregoriev Glacier, a flat-top glacier within the Inner Tien Shan, Kyrgyzstan. Relative carrier-phase GPS surveys reveal a vertical lowering at the summit of the glacier. Based on snow density data and an energy-mass balance model, we estimate that the annual precipitation and summer mean temperature required to maintain the glacier in the current state are 289 mm and −3.8 • C at the glacier summit (46… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 23 publications
1
42
0
Order By: Relevance
“…Since 1997, the climate was the most favourable during measured period due to slight precipitation decrease only, but a temperature decrease during summer months (table 4). Hence, the glaciers might be currently close steadystate in this region, which was also found in a study about Gregoriev ice cap situated close to the Tien Shan station (Fujita et al 2011). However, it has to be considered that glacier area changes as investigated in this study can not directly linked to the climate signal as the area shows a delayed signal to climate only; and the response time of the polythermal or even cold glaciers in this region is likely several decades.…”
Section: Climatic Considerationsmentioning
confidence: 76%
“…Since 1997, the climate was the most favourable during measured period due to slight precipitation decrease only, but a temperature decrease during summer months (table 4). Hence, the glaciers might be currently close steadystate in this region, which was also found in a study about Gregoriev ice cap situated close to the Tien Shan station (Fujita et al 2011). However, it has to be considered that glacier area changes as investigated in this study can not directly linked to the climate signal as the area shows a delayed signal to climate only; and the response time of the polythermal or even cold glaciers in this region is likely several decades.…”
Section: Climatic Considerationsmentioning
confidence: 76%
“…Even for Central Asia, these values are exceptional. Outside the Pamir, such arid conditions can only be found in the most central parts of the Tian Shan, where mean precipitation sums of 296 mm/a were recorded at an elevation of 3614 m asl (Fujita et al, 2011). Earlier applications of the HBV-ETH model (Hagg et al, 2006) have yielded basin values for precipitation of more than 500 mm in the Eastern Tian Shan (Glacier No.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, if the impurities were exposed at the glacier's surface during the melting season, glacial melting would be further accelerated. This could occur if snow melting resulted in the exposure of ILAIs at the glacier's surface and/or if the melting season was reinforced and expanded due to a warming climate (Fujita 2007;Fujita et al, 2011). It was observed that for elevations lower than 4800 m asl on Baishui glacier, there was no snow cover area on glacier's surface during the summer, so those ILAIs remained exposed throughout the summer (Niu et al, 2017b).…”
Section: Carbonaceous Compound Flux and Glacial Retreatmentioning
confidence: 99%